An Alternative Application For Practice Lessons During The Covid-19 Process: Video Demonstrations - YAVAŞ ÇELİK, Melike (Göbeklitepe Medical Science Journal, 2021)
Aim: With this study, it was aimed to evaluate the contribution of the video presentation prepared for the application of invasive procedures in children to the competencies and application knowledge of nursing students. Design and method: The universe of the study was composed of nursing 3rd grade students. The sample consisted of 30 students randomly selected among these students. The video presentation prepared for the invasive procedure application was shared with the students through social media searching, and the contribution of this demonstration to the competence and application knowledge of the students was evaluated. Findings: As a result, students do not find distance education as effective as face-to-face education. However, the video screening applied contributed to the competence and application knowledge of nursing students. Conclusions: The pandemic process has limited the application area of future nurses. However, training with video can close this gap and increase the competencies of nursing students.